Beneficial Effects of Physical Training on the Cardio-Inflammatory Disorder Induced by Lung Ischemia/Reperfusion in Rats - Delbin, Maria Andreia [UNESP]; Couto Davel, Ana Paula; Rossoni, Luciana Venturini; Antunes, Edson; Zanesco, Angelina [UNESP] (Springer/plenum Publishers, 2011)
Our laboratory demonstrated that training program attenuated the inflammatory responses in lung ischemia/reperfusion (IR). Considering the importance of the inflammatory responses on the cardiovascular system, we evaluate the effect of physical training on the vascular responsiveness and its underlying mechanism after lung IR. Male Wistar rats were submitted to run training and lung IR. Concentration-response curves for relaxing and contracting agents were obtained. Protein expressions of SOD-1 and p47(phox), plasma nitritre/nitrate (NO (x) (-) ) and interleukin 6 (IL-6) were evaluated. A decreased in the potency for acetylcholine and phenylephrine associated with an upregulation of the p47(phox) expression were found after Lung IR as well as an increase in IL-6 and NO (x) (-) levels. Run training attenuated the vascular dysfunction that was accompanied by reduction of the p47(phox) protein expression and IL-6 levels. Our findings show the beneficial effect of training on the vascular function that was associated with reduction in inflammatory response in lung IR.
Keywords: physical training; vascular dysfunction; inflammatory responses; lung ischemia/reperfusion